Pembatasan Tanggung Jawab Shopee terhadap Kerugian Konsumen Dihubungkan dengan UU Perlindungan Konsumen (Lembaga Pengembangan Kinerja Dosen, 2025)
The transformation of digital technology has changed people's transaction patterns, especially through e-commerce platforms such as Shopee which has experienced a significant increase in Indonesia. This study aims to analyze the application of exoneration clauses in Shopee's terms and conditions and its conformity with consumer protection laws in Indonesia. The research method used is normative law with a statutory and conceptual approach, using primary legal sources in the form of the Consumer Protection Law, Civil Code, and the Electronic Information and Transaction Law, as well as secondary legal materials from journals and academic literature. The results of the study show that the standard clause that limits liability is not absolutely valid because it has the potential to eliminate the rights of consumers who are protected by law, so that it can be considered null and void according to Article 18 paragraph (3) of the Consumer Protection Law. Shopee's liability is proportional, depending on proof of negligence in identity verification, complaint handling, and system security. Therefore, it is necessary to reconstruct a fairer accountability mechanism through improving dispute resolution mechanisms, stricter government supervision, and strengthening consumer protection in electronic transactions. This research confirms the importance of balancing the business interests of the platform and the protection of consumer rights.